Mechanisms and influencing factors of cultural ecosystem services value realization - Yiqing Lin; Yanbing Liu; Zhiyun Ouyang; Chen Meng; Yi Xiao (Environmental and Sustainability Indicators)
Cultural ecosystem services (CES) play a crucial role in sustainable development, yet research on the mechanisms of CES value realization and its influencing factors remains limited, particularly in understanding how ecological, transportation, and marketing elements interact to realize value. This study employs Travel Cost Interval Analysis (TCIA) combined with statistical analyses to evaluate CES value realization patterns and their influencing factors. The research draws on survey data from 18 scenic areas in Lishui, China, collecting 1624 valid responses across natural, agricultural, and cultural attractions. Results reveal that Lishui's total CES value reached CNY 37.93 billion in 2019, with direct consumption representing the dominant value component. Among different landscape types, natural sites contributed the largest share, highlighting the crucial role of natural landscapes in regional CES value realization. Only high-level (Level 4) transportation and ecological factors significantly enhance CES value realization, while marketing strategies show optimal effectiveness at Level 3. These findings provide valuable insights for sustainable tourism development and ecosystem management. They suggest the need for integrated optimization strategies rather than isolated improvements, emphasizing the importance of threshold effects in infrastructure development and the potential of value-added strategies in ecotourism. The study offers practical guidance for policymakers in balancing ecological preservation with economic development, particularly in regions rich in natural and cultural resources.